Sociological research and urban children and youth - Berman, Rachel; Albanese, Patrizia; Chen, Xiaobei (Sociological studies of children and youth, 2023)
Almost a third of the 4 billion people living in urban areas today are children, according to the United Nations. By 2050, 70 percent of the world's children will live in cities. Yet how has recent sociological work engaged with children and youth living in cities around the world? What does a focus on children and youth in an urban context mean for researchers working within a variety of sociological frameworks? How have children's and youth's experiences shaped and been shaped by the diverse urban scapes and contexts in which they live? Sociological Research and Urban Children and Youth brings together cutting-edge work that addresses children's and youth's urban living experiences as well as the social, political, and ecological realities that accompany this. Featuring contributions from Australia, Canada, the U.K., and the United States, the chapters critically engage with core analytical and conceptual issues ranging from relationality to citizenship and belonging, to power, structure, and agency. Recognizing the potential research with and about young people can have in decision making on multiple levels of policy and service provision, Sociological Research and Urban Children and Youth provides a key foundation for considering the influence of urban environments on young people, and vice versa.